GUARANTEE OF CHILDREN IN CONFLICT WITH THE LAW IN THE PERSPECTIVE OF LEGAL PROTECTION - Muhamad Arif Agus; Johari Johari (Polteknik Ilmu Pemasyarakatan, 2022)
The purpose of this study was to examine and analyze (1) the guardianship arrangements for children in conflict with the law, (2) the ideal arrangements for the guardianship of children in conflict with the law. The research method used is a normative juridical approach. The conclusion of the study The regulation of child guardianship in the Child Protection Law only regulates the protection of children in a civil manner, does not include Children in Conflict with the Law who are being processed in the process of the juvenile criminal justice system, and in the Juvenile Criminal Justice System Act there are no guardianship provisions for Children in Conflict with the Law. The ideal arrangement for the guardianship of children in conflict with the law as regulated in Article 33 of the Child Protection Law, by reconstructing and dividing two guardianship phrases, namely guardianship in the civil aspect which must be carried out through a court decision process, and the criminal aspect whose stipulation directly appoints the institution. or a body that is given the task and authority to carry out guardianship of Children in Conflict with the Law without having to go through a court order. The appropriate institution or body to handle and carry out the guardianship of Children in Conflict with the Law is the Correctional Center (Bapas), because the role of the Fathers has so far been less than optimal, because it is only limited to conducting community research (Litmas) and is finished after reading the results of its Litmas at the trial of children in court